Development Policy and the Nature of Society: Understanding the Kerala Model - T K Oommen (Economic & Political Weekly EPW march 28, 2009 vol xliv no 13, 2009)
The quality of life is usually measured by three interrelated dimensions such as the human development index, the human freedom index, and the human distress profile. In Kerala, in spite of high HDI, the rates of suicide, crime, drug addiction, unemployment, etc, are high compared to other states. This essay argues that a high quality of life should register a high HDI, the maximum HFI and minimum HDP. It is necessary to work towards this complex objective if Kerala wants to sustain its claim to a high quality of life.